2012
DOI: 10.1177/1756287212471096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development of two innovative pharmaceutical forms of leuprorelin acetate

Abstract: Objectives: Two innovative pharmaceutical forms of leuprorelin acetate have been developed as 1-month and 3-month implants for the treatment of advanced hormone-dependent prostate cancer. These products contain active substance dispersed homogeneously in a biodegradable polymer. Here we present the key results from the clinical development of these slow-release implant formulations of leuprorelin. Methods: Two therapeutic studies of the 1-month implant were performed: a randomized, controlled study comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 9 publications
2
29
0
2
Order By: Relevance
“…Studies comparing one and three months formulations showed no relevant differences concerning effects on testosterone levels and PSA [84][85][86][87]. This was also the case for a comparison of three and six months formulations in a mixed population [88].…”
Section: Advanced Prostate Cancermentioning
confidence: 79%
See 2 more Smart Citations
“…Studies comparing one and three months formulations showed no relevant differences concerning effects on testosterone levels and PSA [84][85][86][87]. This was also the case for a comparison of three and six months formulations in a mixed population [88].…”
Section: Advanced Prostate Cancermentioning
confidence: 79%
“…It should be noted that the studies with leuprorelin were performed with various formulations, whereas this was not the case for the other medicines. A specifi cation of the applied formulation was only provided in a few studies: Lupron [17,83], Enantone [18] and Sandoz generic formulation [87]. The 16 other studies did not specify the formulation, although the vast majority of studies used a dose of 7.5 mg per 28 days or 22.5 mg…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damit ist Leuprorelin seit über 30 Jahren das führende GnRH-Analogon und bildet die Grundlage für viele multimodale Therapiekonzepte [11]. Neben der langjährigen Erfahrung der Ärzte mit dem Wirkstoff unterstützen auch sehr umfassende Daten zur Wirksamkeit und Sicherheit von Leuprorelin dessen Einsatz [12,13,14].…”
Section: Diskussionunclassified
“…Das Generikum steht ebenfalls als Fertigspritze zur Verfügung, enthält jedoch ein stäbchenförmiges Implantat, das ohne weitere Vorbereitung direkt injiziert wird. Darüber hinaus gibt es keine Hinweise auf relevante Unterschiede in Hinblick auf Wirksamkeit, Sicherheit, Bioverfügbarkeit oder Lagerung, welche die beobachtete Marktdominanz des Altoriginals erklären würden [13].…”
Section: Diskussionunclassified